Evidence of monotheism in measure and lordship and its impact on the upbringing of children (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad, the master of the prophets, and his family, the guides, his chosen companions, and those who are guided by his guidance until the Day of Judgment.And yet...Evidence for monotheism in management and divinity cannot be comprehended without observing the origin of monotheism, because the oneness of God Almighty arises from His limitlessness, and existence encompasses all perfections and is devoid of every defect and shortcoming.